High Indoleamine 2,3-Dioxygenase Is Correlated With Microvessel Density and Worse Prognosis in Breast Cancer - Wei, Lijuan; Zhu, Shanshan; Li, Menghui; Li, Fangxuan; Wei, Feng; Liu, Juntian; Ren, Xiubao (Frontiers in Immunology, 2018)
Indoleamine 2, 3-dioxygenase (IDO), which catalyzes the breakdown of the essential amino acid tryptophan into kynurenine, is understood to have a key role in cancer immunotherapy. IDO has also received more attention because of its non-immune functions including regulating angiogenesis. The purpose of this study was to investigate the effects of IDO on microvessel density, and to explore its prognostic role in breast cancer. We showed IDO expression was positively correlated with microvessel density (MVD) labeled by CD105 (MVD-CD105) rather than MVD labeled by CD31 (MVD-CD31) in breast cancer specimens. Both IDO expression and MVD-CD105 level were associated with initial TNM stage, histological grade and tumor-draining lymph nodes (TDLNs) metastasis in breast cancer. In the prognostic analysis, TDLNs metastasis, an advanced TNM stage (III) and high histological grade (III) significantly predicted shorter survival in univariate analysis. Concentrating on IDO and MVD, the patients with IDO expression or high MVD level had poorer prognosis compared with no IDO expression (P=0.047 for PFS) and low MVD level (P=0.019 for OS); the patients with IDO expression and high MVD level had a tendency with shorter overall survival when compared with non IDO expression, low MVD level or both (P=0.062 for OS). In multivariate analysis, an advanced TNM stage (III) was significantly associated with shorter 5-year survival rate of PFS (HR: 0.126, 95%CI: 0.024-0.669, P=0.015). In order to verify the phenomenon of IDO promoting angiogenesis, we contained the study in vitro. We detected the expression of IDO mRNA in breast cancer cell lines and measured the concentration of tryptophan and kynurenine in the supernatiants of MCF-7 by high performance liquid chromatography (HPLC). The ratio of Kyn and trp (kyn/trp) was calculated to estimate IDO-enzyme activity. MCF-7 cells, which produce high level of IDO and metabolize tryptophan, promoted human umbilical vein endothelial cells (HUVEC) proliferation significantly in co-culture system. Meanwhile IDO could up-regulate the expression of CD105 in HUVEC, which was down-regulated after adding IDO inhibitor, 1-MT. These results suggest that IDO could promote angiogenesis in breast cancer, providing a novel, potentially effective molecular or gene therapy target for angiogenesis inhibition in the future.